A structure-preserving divide-and-conquer method for pseudosymmetric matrices - Benner, P; Nakatsukasa, Y; Penke, C (Society for Industrial and Applied Mathematics, 2023)
We devise a spectral divide-and-conquer scheme for matrices that are self-adjoint with respect to a given indefinite scalar product (i.e., pseudosymmetic matrices). The pseudosymmetric structure of the matrix is preserved in the spectral division such that the method can be applied recursively to achieve full diagonalization. The method is well suited for structured matrices that come up in computational quantum physics and chemistry. In this application context, additional definiteness properties guarantee a convergence of the matrix sign function iteration within two steps when Zolotarev functions are used. The steps are easily parallelizable. Furthermore, it is shown that the matrix decouples into symmetric definite eigenvalue problems after just one step of spectral division.